Review Dan Analisa Karakteristik Dan Penyebab Kerusakan Sudu Turbin Gas - Yudi Eka Risano (JURNAL MECHANICAL, 2010)
The present study concerns the review and the analysis of malfunctions characteristic and the reasons of moving blade damage. Such malfunctions are breakage of moving blade in excessive temperature conditions, increasing vibration, little cyclic weariness from frequent heat exchange at start-up and shut-down, and erosive deterioration and highly temperature corrosion. The type of damage can be divided on static, fatigue, thermal fatigue, corrosion and erosive.Keywords: gas turbine, moving blade, pressure, temperature, defect.